Reviews in Environmental Science and Bio/Technology - Reviews in Environmental Science and Bio/Technology (Springer Nature, 2026)
The areas of environmental science and environmental (bio)technology are broad, multidisciplinary, fast growing and extremely active. During the last few decades, an overwhelming amount of data has become available, a panoply of discoveries has been made and exciting new environmental technologies have emerged. It is almost impossible to keep up to date on current developments in these areas. Moreover, there is a definite need to extract the quintessence out of this information, to synthesise the research progress and to identify the recent advances in environmental science and technology. This is the rationale behind the journal Reviews in Environmental Science and Bio/Technology.
FI 1.1
Q1
Keywords: Earth; Space & Environmental Sciences; Environmental Science; Ciencia ambiental; Acuerdos transformativos; Transformative agreements; Biotecnología ambiental; Medio ambiente